2021
DOI: 10.1029/2021gl094162
|View full text |Cite
|
Sign up to set email alerts
|

Rupture Process of the 2020 Mw7.0 Samos Earthquake and its Effect on Surrounding Active Faults

Abstract: The M w 7.0 Samos earthquake 11:51 GMT) struck the eastern Aegean Sea in the area between the Samos Island and the western Turkish coasts. The epicenter of the main shock lies about 10 km offshore of the north coast of Samos Island (37.9020°N-26.7942°E; Bogazici University, Kandilli Observatory and Earthquake Research Institute's Regional Earthquake-Tsunami Monitoring Center-BDTIM), and at a focal depth of 10-12 km, according to the majority of the published point source mechanism solutions (Table S1). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Since their calculations are based on a different fault model and aftershock spatial distribution, there is no common ground for comparing their results with ours. On the other hand, great similarities can be observed with the results of Chousianitis and Konca (2021), who also show that the aftershock sequence is exclusively constrained in stress rise areas. However, using the optimum oriented normal receiver-faults in their calculations, instead of ours which involves receiver faults identical to the slipped one (source fault), Chousianitis and Konca (2021) show that the cluster C/"2" (Figures 2 and 3b, respectively) falls entirely in a stress-rise area, in contrast with our results which show that the respective cluster lies in a stress-drop area and, thus, implying a triggered reactivation of a yet unknown smaller fault.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Since their calculations are based on a different fault model and aftershock spatial distribution, there is no common ground for comparing their results with ours. On the other hand, great similarities can be observed with the results of Chousianitis and Konca (2021), who also show that the aftershock sequence is exclusively constrained in stress rise areas. However, using the optimum oriented normal receiver-faults in their calculations, instead of ours which involves receiver faults identical to the slipped one (source fault), Chousianitis and Konca (2021) show that the cluster C/"2" (Figures 2 and 3b, respectively) falls entirely in a stress-rise area, in contrast with our results which show that the respective cluster lies in a stress-drop area and, thus, implying a triggered reactivation of a yet unknown smaller fault.…”
Section: Discussionsupporting
confidence: 72%
“…Concerning the postsequence effects and triggering scenarios on the other surrounding faults, notably the Karlovasi-Fourni and the Kuşadası (Yavansu) faults, and less the Ikaria and Chios-Çeşme faults (the latter shows diverse stress change along its strike), show stress increase, matching the results of Chousianitis and Konca (2021). The other faults show either stress-drop or negligible stress change, matching again the results of Chousianitis and Konca (2021), with the only exception the Karaburun fault which in the results of the latter authors, a low and partial stress rise is demonstrated. It must be noted that triggering or delaying effects on nearby faults due to static stress changes is a relative information which depends on the state of stress in which every fault is (maturity stage) and cannot be used to predict the time of the next rupture.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…(2021), the numerical models' slip has a smaller maximum slip and a deeper location of the modeled maximum slip. The maximum slip in Chousianitis and Konca (2021) is significantly bigger than in the numerical model. For slip from Sakkas (2021) best fits are the models with λ=0.2 $\lambda =0.2$ and λ=0.1 $\lambda =0.1$, at the surface and at a dip distance of 8 km, respectively.…”
Section: Modeling Of the 2020 Samos Mw70 Earthquakementioning
confidence: 65%